Conversation Analytic Role-play Method in Antenatal Screening Conversations (The Convene Study) - Antenatal appointment transcripts - Wagstaff, Jayne; Hamann, Magnus; Bryant, Louise; Ahmed, Shenaz; Stokoe, Elizabeth (University of Leeds, 2021)
This dataset contains transcripts of 27 entire antenatal appointments, based on 27 audio recordings. A convenience sample of midwives and pregnant woman (aged ≥ 16 years) attending their first antenatal booking appointment was obtained within GP practices and hospital clinics. 27 women participated (10 women also attended with their partner who agreed to participate), along with 12 midwives. All present at the appointment gave informed consent, and the researcher remained outside of the clinic room when the recordings were obtained.
Keywords: FOS: Clinical medicine